The study of smoking effect on work performance among staff of Health Department of Malacca, 1996 - Masran Mohamad; Syed Mohamed Aljunid (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A study on prevalence of smoking and its effect on job performance was undertaken among male staff working in Health Department in all districts in the state of Melaka, in March 1996 .It is a cross-sectional study, using self-administered questionnaires. Universal sampling technique was employed in this study. A total of 344 questionnaires were distributed where 313 were completed and returned (91.27%). The findings of the study show that prevalence of smokers is 45.5 %, while 14.1% are ex-smokers. There is significant relationship between smoking status with age of respondents, ethnicity, educational status, years of service and income. The findings of this study also show performance is significantly related to age of respondents, ethnicity, years of service and income. However there is no significant relationship between smoking and job performance. In conclusion, this study shows that prevalence of smokers among male staff is high but it is not an important factor influencing their job performance.